Consideraciones radiológicas del cáncer de pulmón y Covid-19: una mirada oncológica - Cánepa G, Joaquín; Manosalva P, Joaquín; Simonetti I, Carolina; Solo de Zaldívar A, Loreto; Valenzuela T, Guillermo; Carvajal V, Felipe; González M, Jaime (Revista Hospital Clínico Universidad de Chile, 2022)
Patients with SARS-Cov-2 infection and lung cancer have an unfavorable prognosis, characterized by higher rates of respiratory failure, use of invasive mechanical ventilation and higher mortality rates. Due to similarities in affected organs in Covid-19 and lung cancer, the radiological accurate diagnosis has become a challenge for physicians. Radiologic findings of lung cancer, such as parenchymal consolidation, spiculation and microlobulations are not specific. Imaging findings of Covid-19 in patients with lung cancer consist of multiple patchy multifocal bilateral ground-glass opacities and consolidations, being hardly distinguishable from an underlying lung malignancy. Differential radiological diagnosis in patients with lung cancer and Covid-19 must include pneumonitis and lung toxicity caused by chemotherapy, target therapies and radiotherapy. Follow-up and simulation tomography in radiotherapy have become an unexpected ally in the early detection of Covid-19 in asymptomatic stages in lung cancer patients. Patients with lung cancer should have particular considerations due to their high risk and the adverse effects of systemic therapies and radiotherapy.